The Effect of Vitamin E on Oral Mucositis Induced by Chemotherapy in Non-Hodgkin Lymphoma Patients Receiving Chemotherapy - Hermanto, Djoko Heri; Habsari, Indri; Machsoos, Budi Darmawan (Clinical and Research Journal in Internal Medicine, 2020)
Chemotherapy-induced mucositis is a side effect of chemotherapy that often occurs in patients with solid tumors and lymphoma. Oral mucositis can affect nutritional status and the risk of infection, both local and systemic. Antioxidant Vitamin E is beneficial for the prevention and therapy of both oral and gastrointestinal mucositis. Aim: To determine the effect of vitamin E therapy on the incidence of oral mucositis in non-Hodgkin lymphoma (NHL) patients receiving chemotherapy. Methods: This is a single-blind experimental study in 62 NHL patients undergoing chemotherapy who meet the inclusion criteria. Patients who met the inclusion criteria were randomly divided into 2 groups, namely 31 patients (treatment group) received vitamin E 400 mg / IU per day for 7 days and 31 patients in the placebo group. The incidence and grade of oral mucositis were observed on day 7. Statistical analysis used Chi-Square and Mann Whitney test according to the data type. Results: a total of 67% NHL patients were male, most of whom were over 46 years of age and as many as 50% of patients used chemotherapy regimens RCHOP and CHOP. There was an incidence of oral mucositis in 35% in the placebo group and 12.9% in the treated group (p = 0.038). In the placebo group, there were 4.8% of patients with grade 2 and 3 oral mucositis, which was not found in the therapy group. Conclusion: Â treatment with vitamin E in NHL patients undergoing chemotherapy can prevent chemotherapy-induced oral mucositis and prevent its severity.